Theoretical and Methodological Framework of Typologization of Digital Identity - O.A. Persidskaya (Социальная психология и общество)
Objective. The purpose of the article is to develop a theoretical and methodological framework for typologization a person’s digital identity based on the following criteria: 1) the role of the digital environment and digital device; 2) the position of the person’s event center; 3) the position of the center of human self-determination. Background. The digital environment is becoming such a significant sphere of modern man’s existence, that it determines the peculiarity of the social situation of the development of a modern man at different age stages, and determining the cultural and historical specifics of the development of higher mental functions and processes. In accordance with these transformations, a trend in academic research related to the building of a new conceptual framework for understanding a changing person is emerging. The author focuses on the foundations of ideas about the digital identity of the individual, which are formed in socio-psychological and anthropological studies. It is shown that research optics in identifying the content parameters of this identity is often narrowed, which leads to the reduction of a complex, multi–component education – the identity of a person in the digital world – to a separate part, which is not enough to build a complex image of a modern man. Methodology. The methodological basis of the study was made up of general scientific methods of analysis, comparison and typologization. The understanding of the types of digital identity is based on the foundations of the modern interpretation of the Cultural and Historical Approach applied to the peculiarities of the digital environment as a significant sphere of human existence. Conclusions. The theoretical and methodological framework for typologizing the digital identity of a person based on criteria of the role of the digital environment and digital device; the position of the event center of a person; the position of the center of human self-determination is presented A number of types of digital identity are described through set of appropriate scenarios of human behavior in the digital environment: 1) a person with a completed mind; 2) a person with digital physicality; 3) an algorithmic person; 4) a returning person and 5) an information tramp.